MODERNISME DAN REFORMISME MUHAMMADIYAH DALAM PEMBINAAN HUKUM ISLAM DI INDONESIA - Abdul Latif (AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2021)
AbstractMuhammadiyah as one of the largest organizations in Indonesia, has a fairly large share in the development of Islamic law in Indonesia. Muhammadiyah is a modernist religious organization and was born with the spirit of renewal with a purification pattern trying to clean Islam from elements of local culture which it considers as heresy, superstition, and superstition. So that researchers want to describe the pattern of Muhammadiyah in providing guidance on Islamic law in Indonesia by using qualitative research which in collecting data, researchers conduct library research. The researcher concludes that Muhammadiyah's modernism and reformism in the development of Islamic law in Indonesia are carried out by ijtihad as legal extracting directly from the Qur'an and hadith. Muhammadiyah conducts legal istinbat on contemporary masail diniyah through the Majelis Tarjih institution, to explore law directly from the Qur'an and hadith.Keywords: Modernism; Muhammadiyah; Islamic Law Development; Reformism. AbstrakMuhammadiyah sebagai salah satu organisasi terbesar di Indonesia, mempunyai andil yang cukup cukup besar dalam pembinaan hukum Islam di Indonesia. Muhammadiyah merupakan organisasi keagamaan yang modernis dan lahir dengan semangat pembaharuan yang bercorak purifikasi berusaha membersihkan Islam dari unsur budaya lokal yang dianggapnya sebagai bid’ah, tahayul dan khurafat, sehingga peneliti ingin mendeskripsikan pola Muhammadiyah dalam memberikan pembinaan hukum Islam di Indonesia dengan menggunakan penelitian kualitatif yang mana dalam pengumpulan data, peneliti melakukan library research. Peneliti berkesimpulan bahwa modernisme dan reformisme Muhammadiyah dalam pembinaan hukum Islam di Indonesia dilakukan dengan ijtihad sebagai penggalian hukum secara langsung dari al-Qur’an dan hadis. Muhammadiyah melakukan istinbat hukum terhadap masail diniyah kontemporer melalui lembaga Majelis Tarjih, untuk menggali hukum secara langsung dari al-Qur’an dan hadis.Kata Kunci: Modernisme; Muhammadiyah; Pembinaan Hukum Islam; Reformisme.